2015
DOI: 10.1093/hmg/ddv245
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of protocadherin 19 in female epilepsy (PCDH19-FE) lead to allopregnanolone deficiency

Abstract: Protocadherin 19 (PCDH19) female limited epilepsy (PCDH19-FE; also known as epilepsy and mental retardation limited to females, EFMR; MIM300088) is an infantile onset epilepsy syndrome with or without intellectual disability (ID) and autism. We investigated transcriptomes of PCDH19-FE female and control primary skin fibroblasts, which are endowed to metabolize neurosteroid hormones. We identified a set of 94 significantly dysregulated genes in PCDH19-FE females. Intriguingly, 43 of the 94 genes (45.7%) showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
78
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(90 citation statements)
references
References 36 publications
7
78
0
Order By: Relevance
“…In our previous study, we gained indirect evidence of a likely role of nuclear hormone receptors in the pathology of PCDH19-FE (12). To examine this further we took advantage of various breast cancer cell lines including MCF-7.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, we gained indirect evidence of a likely role of nuclear hormone receptors in the pathology of PCDH19-FE (12). To examine this further we took advantage of various breast cancer cell lines including MCF-7.…”
Section: Resultsmentioning
confidence: 99%
“…We have recently shown that neurosteroids may play a significant role in the pathology of PCDH19-FE (12). We found that allopregnanolone levels were low in the blood of PCDH19-FE girls and that genes regulated by estrogen, progesterone and androgen receptors were among the most significantly dysregulated in patient primary skin cells (12). …”
Section: Introductionmentioning
confidence: 99%
“…One hypothesis is that sexually dimorphic genes compensate for the loss of functional Pcdh19 in males. For example, 2 sexually dimorphic genes, AKRIC2 and AKRIC3 , are dysregulated in PCDH19 mutation-positive females [140]. These genes are regulated by steroid receptors and encode metabolizing enzymes for allopregnanolone, a neurosteroid that associates with and modulates GABA A receptors, causing prolonged hyperpolarization and preventing overexcitability.…”
Section: Roles In Behavior and Neurological Or Neurodevelopmental Dismentioning
confidence: 99%
“…These genes are regulated by steroid receptors and encode metabolizing enzymes for allopregnanolone, a neurosteroid that associates with and modulates GABA A receptors, causing prolonged hyperpolarization and preventing overexcitability. AKRIC2 and AKRIC3 mRNA, AKRIC3 protein, and allopregnanolone blood levels are all decreased in patients with PCDH19 mutations [140]. Another hypothesis proposes cellular interference as a mechanism for male sparing in PCDH19 mutation disorders.…”
Section: Roles In Behavior and Neurological Or Neurodevelopmental Dismentioning
confidence: 99%
“…For comparison, we included the clinically relevant drugs clonazepam and ganaxolone. Clonazepam has been used widely as a treatment for anxiety as well as seizure disorders, whereas ganaxolone is currently in clinical trials as an adjunct for the treatment of epilepsy [1719, 26]. Information on the behavioral effects of clonazepam and ganaxolone are available for the drugs alone [2729]; however, mixtures of these drugs have not been evaluated to our knowledge.…”
Section: Introductionmentioning
confidence: 99%